Screening of antibacterial activity of Crown-of-thorns starfish (Acanthaster spp.) extracts using modified microtiter-plate resazurin assay - SHARON ROSE M. TABUGO; TRICKSIE P. BALATERO; RODELYN M. DALAYAP (Society for Indonesian Biodiversity, 2025)
Abstract. Tabugo SRM, Balatero TP, Dalayap RM. 2025. Screening of antibacterial activity of Crown-of-thorns starfish (Acanthaster spp.) extracts using modified microtiter-plate resazurin assay. Biodiversitas 26: 1735-1742. Marine organisms have emerged as promising sources for the discovery of new compounds that have medical application potential. Their ability to thrive in environments teeming with pathogenic microorganisms and predators indicates the production of unique chemical compounds with significant biological activities. This study identified and morphologically characterized Acanthaster spp. (Crown-of-Thorns, COT starfish) from various sites, including microhabitats in Iligan and Panguil Bays, and extracted polar and non-polar crude extracts for antibacterial activity screening. Samples were collected from three locations: Buruun, Iligan City; Samburon, Linamon; and Maigo, Lanao del Norte. Crude extracts were prepared using hexane (non-polar) and methanol (polar) solvents for all samples from the three sites. A modified microtiter antimicrobial assay was performed on all crude extracts, which exhibited antibacterial activity against Pseudomonas aeruginosa (a Gram-negative bacterium) and Staphylococcus aureus (a Gram-positive bacterium). The activity of HMCOT (hexane extract of samples from Maigo, Lanao del Norte) was comparable to Ciprofloxacin (positive control) based on the post-hoc test. Qualitative screening of the crude extracts for secondary metabolites revealed the presence of alkaloids, flavonoids, and saponins, which are likely contributors to the observed antibacterial activity. The diversity of the chemical compounds reflects the biodiversity of the source organisms, which have evolved and adapted to their specific environments. Thus, Acanthaster spp. shows potential for medical research, though further tests are necessary to validate these findings. The results of this study served as baseline data for future research.